Activation of Ca2+-independent membrane-damaging activity in Lys49-phospholipase A(2) promoted by amphiphilic molecules - Bortoleto-Bugs, R. K.; Neto, A. A.; Ward, R. J. (Elsevier B.V., 2004)
Association of class-II phospholipase A(2) (PLA(2)) with aggregated phospholipid substrate results in elevated levels of the Ca2+-dependent hydrolytic activity. The Asp49 residue participates in coordination of the Ca2+ ion cofactor, however, in Lys49-PLA(2) homologues (Lys49-PLA(2)S), substitution of the Asp49 by Lys results in loss of Ca2+ binding and lack of detectable phospholipid hydrolysis. Nevertheless, Lys49-PLA2S cause Ca2+-independent damage of liposome membranes. Bothropstoxin-I is a homodimeric Lys49-PLA(2) from the venom of Bothrops jararacussu, and in fluorescent marker release and dynamic light scattering experiments with DPPC liposomes we demonstrate activation of the Ca2+-independent membrane damaging activity by similar to4 molecules of sodium dodecyl sulphate (SDS) per protein monomer. Activation is accomparlied by significant changes in the intrinsic tryptophan fluorescence emission (ITFE) and near UV circular dichroism (UVCD) spectra of the protein. Subsequent binding of 7-10 SDS molecules results in further alterations in the ITFE and far UVCD spectra. Reduction in the rate of N-bromosuccinimide modification of Trp77 at the dimer interface suggests that initial binding of SDS to this region accompanies the activation of the membrane damaging activity. 1-anilinonaphthalene-8-sulphonic acid binding studies indicate that subsequent SDS binding to the active site is concomitant with the second structural transition. These results provide insights in the structural basis of amphiphile/protein coupling in class-II PLA(2)s. (C) 2004 Published by Elsevier B.V.
Keywords: enzyme mechanism; SDS; fluorescence; Circular dichroism